Global Water Dances in Viçosa/MG: dance and environmental activism - Silveira, Juliana Carvalho Franco da; Fialho, Vinicius Macena Santiago (Urdimento - Revista de Estudos em Artes Cênicas, 2023)
This research aimed to analyze the impacts of the actions of an extension project in dance whose proposal was to participate in the international event Global Water Dances 2021 – involving participants in the planning process, rehearsals, production, and presentation –, to raise awareness and sensitize about the importance of water for the preservation of life. Dance was approached in this context as an articulator of the body-environment relationship and in its political character, in the sense of enabling the opening to new social configurations. Based on the analysis of the impacts of the project's actions, dance was recognized as an epistemology that enabled awareness and social mobilization, as well as the construction of a sense of community.